Extended Performance Research on IEEE 802.11a 54 Mbps Multi-Node Laboratory Links - Carvalho, José Pacheco de (2019)
Wireless communications, involving electronic devices, are increasingly important Performance is a fundamental issue, leading to more reliable and efficient communications. Security is also most important. Laboratory measurements were performed about several performance aspects of Wi-Fi IEEE 802.11a 54 Mbps Open links. Our study contributes to performance evaluation of this technology, using available equipments (HP V-M200 access points and Linksys WPC600N adapters). New detailed results are given, namely at OSI level 4, from TCP and UDP experiments. TCP throughput is measured versus TCP packet length. Jitter and percentage datagram loss are measured versus UDP datagram size. Results are compared for point-to-point, point-to-multipoint and four-node point-to-multipoint links. Conclusions are drawn about performance of the links. © 2018, International Association of Engineers.